The Impact of Monetary Policy on Sharia Stock Prices in Indonesia - Rauzatul Jannah; M. Rasyidin; Azka Rizkina (Electronic Journal of Education, Social Economics and Technology, 2025)
The rapid growth of the Islamic banking sector in Indonesia, marked by the establishment of Bank Syariah Indonesia (BSI) due to the merger of three state-owned Islamic banks, reflects the increasing awareness of the importance of financial transactions based on sharia principles. In this context, monetary policy set by Bank Indonesia plays a crucial role in influencing the financial sector's stability, including the movement of Islamic bank stock prices. This study aims to analyze the impact of monetary policy, represented by inflation and exchange rate variables, on the stock price of Bank Syariah Indonesia from January 2022 to December 2024. The research employs a quantitative approach using multiple linear regression analysis. The F-test results indicate that inflation and exchange rates simultaneously have a significant effect on stock prices. Partially, inflation has a substantial adverse effect, while exchange rates have a considerable positive impact on the stock price of BSI. These findings underscore the importance of stable monetary policy management as a critical reference for investors in making investment decisions in the Islamic banking sector.